Bioactive 3D Bioprinted N,S-Graphene Quantum Dot Reinforced Nanocellulose/Fucoidan Scaffolds for Wound Healing - Çiftçi, Fatih; Sillanpää, Mika (Elsevier, 2026)
The development of printable bioinks that simultaneously possess superior rheological fidelity and multifunctional bioactivity remains a critical challenge in extrusion-based 3D bioprinting for tissue engineering. Herein, we engineered a novel nanocomposite hydrogel scaffold comprising a structural Cellulose Nanofiber (CNF) backbone and a bioactive Fucoidan (FUC) matrix, reinforced with hydrothermally synthesized Nitrogen and Sulfur co-doped Graphene Quantum Dots (N,S-GQDs). Comprehensive physicochemical characterization confirmed the successful integration of ultrasmall (~9.28 nm), crystalline N,S-GQDs into the polymer network. Rheological analysis revealed that the incorporation of GQDs significantly modulated the viscoelastic properties; all formulations exhibited characteristic non-Newtonian pseudoplastic (shear-thinning) behavior beneficial for extrusion, while the storage modulus (G') consistently dominated the loss modulus (G") across the frequency range, indicating the formation of a stable, solid-like gel structure with enhanced shape fidelity post-printing. Beyond mechanical reinforcement, the nanocomposites demonstrated exceptional biological functionality. The optimized scaffolds exhibited potent, dose-dependent antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, alongside a significant anti-inflammatory efficacy characterized by a 78.4% inhibition of protein denaturation. In vitro biological assessments revealed a transition from passive biocompatibility to active regeneration; the scaffolds induced a remarkable proliferative response in L929 fibroblasts, with cell viability exceeding 140% over 14 days. Furthermore, in a proliferation-independent scratch assay, the GQD-functionalized hydrogels significantly accelerated fibroblast migration, achieving near-complete wound closure (99.8%) within 48 h compared to 55.3% in the control group. These findings collectively establish the 3D printed CNF/FUC/N,S-GQD hydrogels as a robust, rheologically tunable, and bioactive “all-in-one” platform for advanced wound healing strategies.
Keywords: 3D bioprinting; Bioink; Graphene Quantum Dots; Nanocellulose; Biocompatible Hydrogels; Tissue Engineering